PERILAKU KONSUMEN DALAM MEMBELI TAS WANITA DI TOKO ONLINE ZALORA - Suyatin, Lusia Huring, Robin Jonathan (EKONOMIA, 2016)
Online shopping is a process where the consumers directly buy item or services from sellers in real-time, without intermediary service. This system can enable customers to transact, but contained some risks, such as the quality of the item does not comply with description on the website, and susceptible to fraud cases because buyers and sellers are not met in person. It has an impact on consumer buying decisions. Consumers who already have a sense of not believing in quality of the product would be hard to make the decision to buy at the same online store. The aim of this study was to determine whether the beliefs and product display influence the decision to buy women’s bag in Zalora Online Store. The hypothesis stated that the confidence and product display significantly influence the decision to buy a women’s bag in Zalora Online Store. 50 women were the respondents in this study. Data were collected by online questionnaire. The collected data were statistically analyzed by multiple linear regression analysis. The analysis showed that the beliefs and product display influence buying decision with the significant value 0.000. t test analysis to examine the effect of beliefs and display products to the buying decision separately showed the significant value were 0001 (X1) and 0032 (X2). The findings of this study indicate that the beliefs and product display influence the decision to buy women’s bag in Zalora Online Store, either together or partially. Before shopping, consumers are generally quite selective to choose the products to be purchased such as attention to brand products as well as the variations of bags. Once consumers buy and getting good service from the Zaloran Online Store such as timeliness of delivery, appropriateness of products with the information on the website, consumers will instill a sense of beliefs that it will influence the consumer's decision to buy a product in Zalora Online Store again.